Design of an analytical fault tolerant attitude determination system using Euler angles and rotation matrices for a three-axis satellite. (April 2014) - Bolandi, Hossein; Abedi, Mostafa; Nasrollahi, Saeed
This article presents a fault tolerant attitude determination system for a three-axis satellite including a sun sensor and a magnetometer. The suggested methodology is developed based on all possible rotations between reference and body frames and computation of Euler angles by them. Using the resulted Euler angles, some variance measures have been derived that offer a solution for analytical model-free fault detection. It is demonstrated that by categorizing different computation methods, the contaminated measurement data could be isolated. Also, utilizing the methods in which the contaminated data are not used, we can continue to provide correct Euler angles. The cited features provide a fault tolerant attitude determination system that always generates the correct attitude angles for attitude control purposes. Since these algorithms are model-free, the fault detection and isolation in the attitude determination system is accomplished independent of the health status of actuators in the attitude control system. In this article, through extensive simulation studies, the desired performance and accuracy of the outlined methods are demonstrated.